Microwave Incinerated Rice Husk Ash Influence on Foamed Concrete Workability - Ridho Bayuaji (Jurnal Aplikasi Teknik Sipil, 2014)
This paper presents the study of Microwave Incinerated Rice Husk Ash (MIRHA) Influence on Foamed Concrete (FC) Workability. The mix proportion of the MIRHA FC was designed using the Taguchi method with L16 orthogonal array with five parameters, namely, MIRHA contents, water cementitious ratio (w/c), sand cement ratio (s/c), superplasticizer (SP) content, and foam content. The workability of the foamed concrete was evaluated through spread measurement in accordance with ASTM-230. The results showed that FC incorporating MIRHA shows lower spread result than normal FC. MIRHA content has contribution 5-15% for workability which a stabled and consistent FC could be achieved. The contribution of MIRHA parameter to achieve the required workability of FC was 12.06%.